Asas Dissenting Opinion Pada Pembuktian Perkara Dalam Putusan Pengadilan Tata Usaha Negara Tentang Sengketa Kepegawaian - Sainul; Rima; Salim, Choirul (IAIN Metro, 2022)
The occurrence of differences of opinion is very likely to occur as a consequence of holding trials with the composition of the panel of judges. As happened in the employment dispute case at PTUN Bandar Lampung Number 7/G/2020/PTUN.BL. Where the plaintiff filed an objection regarding the object of the dispute which was decided when the plaintiff was still a Candidate for Civil Servants and did not have a certain position but only obeyed his superiors. The plaintiff received administrative sanctions for crimes that were considered disproportionate to the crimes committed by his superiors. Of the three judges who received and examined this case, there was one judge who had a dissenting opinion in deciding the case. Therefore, the researcher conducted an in-depth analysis of the differences in opinion of the judges. The result of this study is that if there is a difference of opinion between the judges in the PTUN decision on employment disputes, voting or the most votes are taken according to the principle in determining a decision if there is a dissenting opinion.